Mini-ATX computer system in vehicle - shihab, m.sami; Zeki, Akram M. (2014)
The aim of this study is to create and assemble the system with customizing/building Linux kernel and environments to be compatible and efficient on mini-ITX computer. The objective of the study is to create/customizing lightweight operating system using GNU/Linux to be used on computer to be used on vehicle. The system would also optimize the size and functionalities most probably would be implemented on car computer system.